Epidemiology and outcome of burn injuries in tertiary care hospital of Northern India - Abrol, Ram Kishan; Mahajan, Savita; Mahajan, Som Raj; Chauhan, Madhu; Singh, Manish KR; Sharma, Manu Priya; Abrol, Surbhi (International Journal of Research in Medical Sciences, 2017)
Background: Burns represent a serious problem around the world especially in low and middle income countries. The aim of this study was to determine epidemiological characteristics, causes and mortality rate of burn deaths in tertiary care hospital of N India as well as to guide future education and prevention programs. Methods: A one year cross-sectional study of all burn patients admitted in Dr. RPGMC Tanda, Kangra, Himachal Pradesh, India was conducted between January 2014-December 2014. Results: Our study revealed that type II (absence of sutural bones) was commoner than type I (presence of type I) asterion. Total of 210 burn injury patients were admitted majority were males[54.5%] and females were [45.5%] males sustained burn injuries mostly at their work place with electric burns whereas females sustained burn injuries at home with cooking appliances. Conclusions: Burn injuries can be reduced by bringing about regulations to develop safer cooking appliances, promoting less inflammable fabrics to be worn out at home and educating the community especially women.